Efficiency of cortexin under the conditions of experimental chronic brain ischemia - Demchenko, A. V.; Belenichev, I. F.; Демченко, Аліна Вікторівна; Бєленічев, Ігор Федорович (Pleiades Publishing, 2016)
Chronic brain ischemia was accompanied by decreased activities of glutathione-dependent enzymes and an increased content of nitrotyrosine in the rat brain, which indicates the development of oxidative and nitrosative stress and a decline of cognitive functions. Treatment with cortexin normalized the activities of glutathione-dependent enzymes, increased the contents of intermediates of the thiol–disulfide system, decreased the level of nitrotyrosine, which is a marker of nitrosative stress, and improved memory.
Keywords: chronic brain ischemia; thiol–disulfide system; glutathione; nitrotyrosine; cognitive functions; cortexin